Immunological and serological profiles in subacute sclerosing panencephalitis: insights from igg and igm analysis in cerebrospinal fluid (Herald of the National Children's Medical Center, 2025)
Background. Subacute sclerosing panencephalitis (SSPE) is a progressive neurodegenerative disor- der caused by persistent measles virus infection. Immunological and serological changes, particularly the presence of measles-specific IgG and IgM in cerebrospinal fluid (CSF) and serum, play a critical role in diagnosis and disease progression.Materials and methods. This study analyzed IgG and IgM levels in the CSF and serum of 45 SSPE patients (32 males, 13 females) using enzyme-linked immunosorbent assay (ELISA). A systematic review of PubMed, Scopus, and Google Scholar was conducted to compare findings with existing literature. Statistical correlations between immunoglobulin levels and patient characteristics were evaluated.Results. IgG levels remained consistently elevated across all patients, while IgM levels varied signif- icantly. A weak correlation between IgG and IgM was observed, suggesting independent immune response mechanisms. Comparisons with previous studies confirmed the role of intrathecal IgG production and measles-specific antibody presence as key diagnostic markers.Conclusion. The findings support the clinical utility of IgG and IgM profiling in SSPE diagnosis. While IgG is a stable diagnostic marker, IgM variability may indicate ongoing immune activation. Further research is needed to explore immunogenetic factors influencing disease progression.
Keywords: subacute sclerosing panencephalitis (SSPE); Measles virus; Cerebrospinal fluid (CSF) analysis; IgG and IgM serology; Intrathecal antibody production